EFISIENSI PEMBIAYAAN AGRIBISNIS BANK SYARIAH DI INDONESIA PADA MASA PANDEMI COVID-19 - Ika Nazilatur Rosida; Muhammad Yazid; Mustofa Mustofa (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The agricultural capital is the main factor in the agribusiness problems.This research employed correlational and descriptive qualitative methods.This research aims to describe the efficiency of the sharia banks inagribusiness financing. Also, it gives the contribution of agribusiness insupporting the economy in Indonesia during covid-19 pandemic. Theresults show that Sharia Bank financing experienced a remarkableincrease during the covid-19 pandemic. Sharia bank financing isconsidered the best choice to deal with fluctuations in the harvest priceand speculation of harvest. The agricultural sector's contribution to theeconomy has always increased during the covid-19 pandemic.